KESALAHAN BERBAHASA PADA MAKALAH MAHASISWA THAILAND UNIVERSITAS ISLAM DARUL ULUM LAMONGAN - Laila Tri Lestari; Anisa Ulfah; Miss Firda Hinna; Nur Zumaisaroh (Pendidikan Bahasa dan Sastra Indonesia, 2021)
This study aims to describe language errors in terms of spelling and effective sentences in Thai student papers at Unisda Lamongan which was carried out with a qualitative descriptive approach. The data sources of this study were obtained from Thai students, especially in the Department of Indonesian Language and Literature Education who studied at Unisda Lamongan, totaling five students. The collection techniques carried out by researchers are reading techniques and note-taking techniques. Data collection instruments using student papers and corpus data sheets. While the data analysis techniques used in this study were data selection, identification of language errors, classifying errors, analyzing data, and concluding the results. Based on the results of research conducted by this researcher, Thai students' papers at Unisda Lamongan found spelling errors, redundancies, incoherence, and illogicalities. Spelling errors, namely: (1) errors in writing capital letters and italics, (2) errors in writing prepositions in (3) writing errors in punctuation, including: (a) errors in the use of periods, (b) errors in the use of commas, (c) ) errors in the use of hyphens, and (d) errors in the use of question marks. Sentence redundancy, there is an excessive use of two conjunctions, the use of words have the same meaning, excessive use of the subject, and the use of formed words and their meanings. Incoherence in sentences, there is the use of conjunctions and excessive use of conjunctions about. The illogicality of the sentence, there is the use of words that cannot be accepted by common sense.